2020
DOI: 10.3126/jnphyssoc.v6i2.34866
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis for seismic wave in Kathmandu valley after Gorkha Earthquake-2015, Nepal

Abstract: We applied the multiscale signal processing technique, the Wavelet Transform Modulus Maxima (WTMM) to characterize high frequency properties of strong motion waveforms, in particular the temporal distribution and strength of singularities in Gorkha earthquake, 25th April 2015. We first explored their relation to earthquake data source. Then we applied the WTMM analysis to strong motion recordings. These showed that the timing and exponent of singularities measured by the WTMM method on the ground motion wave f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Similarly, from the multifractal study of seismic signal of Gorkha earthquake, smoother seismic signal was noticed with growing distances and the time duration of main event was noticed to be very short [9]. A group of researchers [10] studied the finite rupture processes and the associated 3D ground motion of the Gorkha earthquake and Dolakha earthquake and concluded that the different rupture features between these events could be related to difference in fault zone structure.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, from the multifractal study of seismic signal of Gorkha earthquake, smoother seismic signal was noticed with growing distances and the time duration of main event was noticed to be very short [9]. A group of researchers [10] studied the finite rupture processes and the associated 3D ground motion of the Gorkha earthquake and Dolakha earthquake and concluded that the different rupture features between these events could be related to difference in fault zone structure.…”
Section: Introductionmentioning
confidence: 95%